On weak laws of large numbers for maximal partial sums of pairwise independent random variables - Thành, Lê Vǎn (Comptes Rendus. Mathématique)
This paper develops Rio’s method [11] to prove the weak law of large numbers for maximal partial sums of pairwise independent random variables. The method allows us to avoid using the Kolmogorov maximal inequality. As an application, a weak law of large numbers for maximal partial sums of pairwise independent random variables under a uniform integrability condition is also established. The sharpness of the result is illustrated by an example.